2004
DOI: 10.1016/j.febslet.2004.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Expression and biochemical analysis of the entire HIV‐2 gp41 ectodomain: determinants of stability map to N‐ and C‐terminal sequences outside the 6‐helix bundle core

Abstract: The folding of HIV gp41 into a 6-helix bundle drives virus-cell membrane fusion. To examine the structural relationship between the 6-helix bundle core domain and other regions of gp41, we expressed in Escherichia coli, the entire ectodomain of HIV-2 ST gp41 as a soluble, trimeric maltose-binding protein (MBP)/gp41 chimera. Limiting proteolysis indicated that the Cys-591-Cys-597 disulfide-bonded region is outside a core domain comprising two peptides, Thr-529-Trp-589 and Val-604-Ser-666. A biochemical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…By contrast, these sequences would become apposed at the membrane-interactive end of the fusion-activated trimer of hairpins by formation of the 6HB. Consistent with this idea, extension of the 6HB core to include residues 528 -535 of the polar segment and residues 669 -677 of the MPR confers stability to a trimer of hairpins model protein (53).…”
supporting
confidence: 59%
See 3 more Smart Citations
“…By contrast, these sequences would become apposed at the membrane-interactive end of the fusion-activated trimer of hairpins by formation of the 6HB. Consistent with this idea, extension of the 6HB core to include residues 528 -535 of the polar segment and residues 669 -677 of the MPR confers stability to a trimer of hairpins model protein (53).…”
supporting
confidence: 59%
“…Alanine Scan of the Fusion Peptide-proximal and Membraneproximal Regions of HIV-1 AD8 gp41-Previously, we found that extension of the 6-helix bundle core of gp41 to include Ala 528 -Leu 535 , of the N-terminal polar segment, and Phe 669 -Ser 677 , within the MPR, conferred stability to a model of the HIV-2 ST gp41 trimer of hairpins, MBP/gp41 (53). In this paper, we examined the functional relevance of these sequences following alanine replacement of component amino acids that are conserved in HIV-1, HIV-2, and SIV ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1), suggesting that hydrophobic contact between the glycine-rich segment and other TM regions is a conserved feature of fusion function. For example, the homologous N-terminal sequence of HIV-2 gp41 cooperates with the membrane-proximal segment in stabilizing the trimer of hairpins (32). The membrane-proximal segment of gp41 contains an aromatic cluster that may interact with hydrophobic residues of the glycine-rich segment in a late fusion intermediate to drive the pore expansion phase of fusion (40,44 Fusion function was also blocked by the five Gly-to-Pro substitutions with position-dependent effects on the various phases of membrane fusion.…”
mentioning
confidence: 99%